Gender Issue and Water Management in the Mediterranean Basin, Middle East and North Africa - Giulia Minoia (Fondazione Eni Enrico Mattei (FEEM), 2007)
This article aims to investigate some aspects of the social process related to water resources management and gender relations. Given that gender and water management are interrelated issues exposed to a growing attention at the international level, it is therefore necessary to identify relations between the academic literature, the institutional framework and the field-based research. This document has been inspired by the Nostrum DSS project (Network on Governance, Science and Technology for Sustainable Water Resources Management in the Mediterranean), a Co-ordination Action funded by the European Commission, which involves eighteen partners from the North and South shores of the basin. As the scope of the project is to disseminate Best Practice Guidelines for the design and implementation of Decision Support System tools (DSS) to identify optimal water resources management regimes, this article is proposing an analysis of a particular geographical and social frame related to the social actors involved in the project, but there are no connections between the paper and the project itself. To create a network between science, policy and civil society is one of the main objectives of the project in order to reach an improved governance and planning in the field of sustainable water management. Therefore, to investigate gender sensitivity in some areas of the basin shall provide a clue. This overview of academic and institutional background refers to a particular geographical and cultural area, the Middle Eastern and North African region. In the first section lies the theoretical background, that has been extrapolated from international organisations guidelines and scholars publications. The second section is specifically focused on the Egyptian geographical context. The first paragraph presents a review of the guidelines suggested by international organisations related to policies on gender and water, as parts of the changes that the global scenario has recently been facing, with the shift from the micro level to the macro level. The second paragraph then describes the side effects of these overspread trends, which are identified in their missing relations with the social context of the intervention. The third and fourth paragraphs introduce the issue of womens role in water management in the Middle Eastern and North African Regions, while highlighting relations between womens involvement in the public sphere and the role they cover in local communities organisations. The proportion of the political representation faced by women in this region is also discussed, tackling their overspread participation in agriculture and their unrecognised working status. The fifth paragraph of this paper will discuss a case study in Egypt, concerning an initiative promoted by international donors and the government aimed at increasing community participation in the design and management of irrigation canals. The case study gives a concrete sample to discuss plusses and problems of womens participation in water users organisations, synthesising many of the theoretical issues that have been raised in the first three parts of this article.
Keywords: J16; Z13; 330; Irrigation; Gender; Regional Development Policy; Wasserpolitik; Geschlecht; Bewässerung; MENA-Staaten